(untitled) (Research, Society and Development, 2020)
Objective: To understand the causal attributions of the evolution and pathophysiology of Diabetic Nephropathy in patients with susceptibility factors. Methodoly: This is an integrative literature review. Electronic databases were searched in the Latin American and Caribbean Center for Health Sciences Information (BIREME), Virtual Scientific Electronic Library Online (SciELO), US National Library of Medicine National Institutes of Health (PubMed). The aptitude parameters were scientific articles indexed in the period from 2010 to 2020, recorded in English, Portuguese or Spanish. Results: In the elaboration of the integrative review it was observed in the vast majority of articles, the prevalence of the type and strength of evidence III, showing intermediate evidence in the relationship of diabetic nephropathy and its risk factors. The approach emphasized diabetic nephropathy by assessing the prevalence of its risk factors and emphasizing the importance of early detection of these associated aspects, envisioning the quality of life for society. Conclusion: The data obtained through the integrative review exposes that Diabetic Nephropathy is in constant prevalence and incidence, related to several risk factors of chronic diseases to eating habits, emphasizing the importance of early detection of these aspects in order to avoid and delay renal complications due to Diabetes Mellitus and consequently decrease the chances of mortality morbidity in cases of progression to DN.